PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN JENJANG KARYAWAN TERHADAP KINERJA PEGAWAI - Muhammad Robi’ Nurwahyud (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2016)
The influence of leadership, work environment and the level of employees of the performance of employees at the Pos Office Agent UGMYogyakarta and the main objective of this research is to test the influence of motivation, leadership, communication, and rewards together and in partial of the performance on the data collected from 30 respondents.Together factors leadership, work environment, and the level of employees have had a positive impact and significant of the performance of employees which evidenced by constant value 3.527 and f-hitung = 3,001 and greater than f-tabel = 2,780. Leadership have had a positive impact and significant of the performance of employees which evidenced by the magnitude of the regression coefficient 0,401 and t-statistik = 2,317 and greater than t-tabel = 1,725. Work environment have had a positive impact and significant of the performance of employees which evidenced by the magnitude of the regression coefficient 0,411 and t-statistik = 2,249 and greater than t-tabel =1,725. The level of work have had a positive impact and significant of the performance of employees the Pos Office Agent UGMas evidenced by the magnitude of the regression coefficient 0,411 and t-statistik = 0,2304 and greater than t-tabel =1,725.